Competitiveness of animal protein exports from Brazil and its relationship to sustainability - Binotti, Francieli; Bertolini, Geysler Rogis Flor (Revista de Contabilidade do Mestrado em Ciências Contábeis da UERJ, 2023)
This study aims to analyze the impact of sustainability on the competitiveness of exports of the Brazilian animal protein market (chicken, beef, and pork), in the period from 2000 to 2021.The Constant Market Share (CMS) method was used, dividing the analysis into sub-periods. The country’s sustainability was assessed by social performance, using the Human Development Index (HDI) and by Environmental Performance, assessed from the Genuine Net Savings (ANS). The results show that Brazil is competitive in the international animal protein market and has been increasing its share over the years, standing out as an important food supplier to the world. With the arrival of the pandemic in 2020, a reduction in Brazilian exports was expected, due to increased restrictions to combat the Coronavirus, but exports of beef and pork were not affected, only chicken meat had a reduction, in 2020, in the value exported and which was surpassed in the following year. The environmental and social dimensions did not show great influence on competitive performance; factors such as world growth, export destinations and trade barriers exerted greater influence on the country’s export performance. This research contributes to broadening the understanding of the relationship between the use of sustainability strategies for Brazil’s competitiveness, and the theoretical subsidies will allow the country and meat exporting companies to adapt their sustainability strategies for a more competitive performance. By demonstrating the relationship between the variable sustainability and exports more clearly, it is possible to better target public policies for the promotion of the Brazilian market.